Reconstructed Marine Fisheries Catches at a Remote Island Group: Pitcairn Islands (1950–2014) - Coghlan, Amy R.; White, Rachel; Dawson, Terence P.; Irving, Robert A.; Zeller, Dirk; Palomares, Maria L. D. (Frontiers in Marine Science, 2017)
The remote Pitcairn Island Group in the South Pacific was designated one of the world’s largest marine reserves in 2016, encompassing some of the few remaining near-pristine areas within EEZ boundaries. Pitcairn's domestic fisheries are small-scale, and consist mainly of subsistence (non-commercial) and limited artisanal (commercial) catches. There is no locally-based industrial (large-scale commercial) fishery and the level of foreign industrial activity in recent times has been minimal, due in part to the low biomass of commercially valuable species, along with economic constraints of the EEZ’s geographic isolation. Using a catch reconstruction method we estimated the total domestic marine catches for the Pitcairn Islands from 1950 to 2014. We show that overall the Pitcairn Islands’ small-scale fisheries catches were almost 2.5 times higher than the data reported by the Food and Agriculture Organization (FAO) of the United Nations on behalf of the Pitcairn Islands, however, this primarily reflects discrepancies prior to the 1980s. Overall, catches for the subsistence and artisanal sectors started with around 12 t∙year-1 in 1950, but declined to 4 t∙year-1 by 2014. Domestic reconstructed subsistence catch levels were entirely driven by changes in the human population on the island, with reconstructed artisanal catches only occurring in recent years (2000 onwards). Industrial fishing is entirely executed by foreign vessels, this catch is considerably variable throughout the years and ceases entirely in 2006. The implementation of the world’s largest marine reserve surrounding the offshore waters of Pitcairn Island has been specifically designed not to affect the rates of subsistence and artisanal fishing conducted by the resident population. Although there is no industrial fishing in the Pitcairn EEZ at present, climate change is predicted to influence the routes of migrating commercially-targeted species, potentially altering fishing effort levels and shift target fishing zones. Implementation of MPAs such as the Pitcairn Island Marine Reserve protect large oceanic areas from risk of future industrial exploitation, whilst protecting near-shore reef and deep-water zones, maintaining domestic coastal fisheries vital for local communities.